CONSTRUCTIVE PECULIARITIES OF MACHINES OF MULTIPLE TORSION. Part 2 - A. V. Vendeneev (Литьë и металлургия)
Analysis of modern tendencies of development of high-speed twisting machines for hardware branch is carried out. the presented review shows that development of perspective types of equipment for production of strands, cables and metal cord is not finished and creation of highefficiency and economical twisting machines is being continued.